The influence of public investment on the German current account surplus - Sonja Jovicic; Galina V. Kolev (Institut der deutschen Wirtschaft (IW), 2019)
The current account surplus in Germany has grown rapidly especially since the early 2000s and this development has been widely criticised. One of the recommendations of the European Commission and other institutions is to increase public investment as a means to reduce the current account surplus. Indeed, Germany needs a broad investment programme in the field of infrastructure, digitalisation and education, and considering the low interest rate there cannot be better times for it. However, as the discussion in this paper suggests, public investment can barely be an instrument to target current account balance. Raising public investment by half of the current level is associated with a decrease of the current account surplus by only 1.3 percentage points after ten years and the effect on the deficit of the trading partners is as low as 0.1 percentage points.
Keywords: 330